A new species of ice cream cone worm in the Gulf of California (Annelida, Pectinariidae) - Tovar-Hernández, María Ana; de León-González, Jesús Angel (Biodiversity Data Journal, 2022)
Background Pectinaria Lamarck, 1818 is composed of 30 species, three of them were originally described from the west coast of the USA and Mexico: P. californiensis Hartman, 1941 (from Redondo Beach, California, USA), P. newportensis Hartman, 1941 (from Newport Bay, California, USA) and P. hartmanae Reish, 1968 (from Bahia de los Angeles, north-western Gulf of California, Mexico). New information A new pectinariid polychaete, Pectinaria santii sp. n., is reported from the central-eastern Gulf of California, Mexico. Pectinaria santii sp. n. is clearly distinguished from its congeners by a combination of the following morphological features: segment 4 with a ventral crest with six horn-shaped anterior projections; three chaetigers with notopodia (S5, S6 and S7); 12 chaetigers with noto- and neuropodia (from S8–19); 8–10 golden opercular paleae per lobe; a pair of ear-shaped lobes at the base of the cephalic veil; an anterior row of chaetae on notopodia with a deep incision and a bifid process at the lateral end of the shaft; and 13–21 pairs of amber scaphal hooks with distal margin rounded and hooded. A full description, including variation and photographs in live and fixed specimens, is provided, as well as a key to the species of Pectinaria from the Tropical Eastern Pacific and Temperate Northern Pacific.
AnnelidaBase. Includes taxonomic key to species of Pectinaria from the Tropical Eastern Pacific and Temperate Northern Pacific.